The path to tuberculosis elimination: a renewed vision - Migliori, Giovanni Battista; Dowdy, David; Denholm, Justin T; D'Ambrosio, Lia; Centis, Rosella (The European respiratory journal, 2023)
Tuberculosis (TB) elimination and pre-elimination, with thresholds of 1 and 10 incident cases per million population, respectively, were considered achievable for low TB incidence countries in the 1990s, when they were conceived. However, it has since become clear that, even in low TB incidence settings with effective programmes and sufficient resources, achieving pre-elimination in the next decade will require a dramatic acceleration of efforts. In this review, we describe the history of the TB elimination concept and existing country experiences, as well as the interventions available to accelerate the progress towards this threshold. We then propose a framework for near-term progress towards the more aspirational goal of TB pre-elimination. This framework consists of five stages (high incidence, moderate incidence, low incidence, nearing pre-elimination and pre-elimination) that are benchmarked to specific levels of TB incidence in each country. Using this framework, countries can set 5-year targets of achieving certain reductions in TB incidence and/or reaching the next stage, through the use of strategies tailored to both local epidemiology and available organisation and infrastructure. TB elimination remains as an aspirational goal in all stages, but certain activities can be prioritised in the short term to make more rapid progress, ensure local-level buy-in and increase accountability. As TB pre-elimination is approached, certain ethical and social concerns are likely to rise in importance; these concerns are also discussed. Our aim in setting this framework is to guide clinicians, public health experts and decision makers in taking actionable next steps in the trajectory towards TB pre-elimination and elimination.